Exploring individual differences as factors to maximize interactive learning environments for future learning. Issue 4 (19th May 2019) - Goh, Joelene; Truman, Barbara; Barber, Daniel
ABSTRACT: Identifying characteristics of individuals who will be negatively impacted by interactive learning environments (ILE) was explored in a field study conducted among learners whose high-stakes performance depended upon grasping training scenarios quickly. Gauging the appropriateness of computer-based simulations for individuals became a pedagogical theme, and examining whether the history of technology usage was a factor revealed what may negatively impact an individual's stress and workload and therefore hinder learning. This study found that individuals reporting higher frequency of computer usage experienced more temporal demand, and reported higher virtual world usage predicted a decrease in temporal demand. Implications suggest continual development of digital literacy skills to prepare for using ILEs especially for faculty and instructors. Establishment of consistent nomenclature of virtual technology terms will improve reliability and validity of measures. Areas of future research include inquiry into digital leadership for promoting metacognition and self-efficacy.